Comparative Study of Corneal Endothelial Cell Damage after Femtosecond Laser Assisted Deep Stromal Dissection. (10th July 2014) - Liu, Ting; Zhang, Jingjing; Sun, Dapeng; Sui, Wenjie; Zhang, Yangyang; Li, Dongfang; Chen, Zhaoli; Gao, Hua
Abstract : Purpose. To find a relatively safe designed stromal bed thickness to avoid endothelial damage for lamellar keratoplasty with an Allegretto Wavelight FS200 femtosecond laser. Methods. Twelve rabbits were randomly divided into 50  μ m and 150  μ m groups according to the anticipated residue stromal bed thickness preparation with a femtosecond laser. Six rabbits without laser cutting were used as a control group. Central endothelial images were analyzed with in vivo confocal microscopy and scanning electron microscopy. The apoptosis of endothelium was evaluated with Hoechst 33342 staining and a TUNEL assay. Results. The endothelium of the 50  μ m group had extensive injuries upon in vivo confocal and scanning electron microscopic observation, and minor injuries were observed in the 150  μ m group. Moreover, more apoptotic cells were observed in the 50  μ m group. Conclusions. When using a FS200 femtosecond laser assisted anterior lamellar keratoplasty, there was minor endothelium damage with a 150  μ m stromal bed, and a more than 150  μ m thickness stromal bed design may prevent the damage of corneal endothelium.